2013
DOI: 10.1364/ol.38.000869
|View full text |Cite
|
Sign up to set email alerts
|

Photonic measures of helicity: optical vortices and circularly polarized reflection

Abstract: For both paraxial and nonparaxial light, numerous electromagnetic quantities are expressible in terms of photon annihilation and creation operators. Accordingly, measures of energy, angular momentum, and chirality acquire a consistent interpretation. From the photonic nature of light, it emerges that an infinite hierarchy of spin-type measures depend on a difference in number operators for modes of opposing helicity, with pure circular polarization giving maximal values. Measures of orbital angular momentum ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…This might be achieved, for example, by best-fitting the dispersion curve to a suitable line-shape function, running the residuals into a log-log plot against wavelength, and recognizing a -4 gradient. A similar effect could also, in principle, arise spate of publications [28][29][30][31] has shown, curious anomalies can arise with circularly polarized light, in the vicinity of a mirror upon which it has normal incidence. As a result of the superposition of forward and backward propagating light, the relative strengths of the electric and magnetic fields are then found to vary over distance, within the space of a wavelength.…”
Section: Discussionmentioning
confidence: 84%
“…This might be achieved, for example, by best-fitting the dispersion curve to a suitable line-shape function, running the residuals into a log-log plot against wavelength, and recognizing a -4 gradient. A similar effect could also, in principle, arise spate of publications [28][29][30][31] has shown, curious anomalies can arise with circularly polarized light, in the vicinity of a mirror upon which it has normal incidence. As a result of the superposition of forward and backward propagating light, the relative strengths of the electric and magnetic fields are then found to vary over distance, within the space of a wavelength.…”
Section: Discussionmentioning
confidence: 84%
“…57,58 It is interesting to note that other aspects of photophysics being markedly modified in the proximity of a mirror have also recently received attention in connection with chiral species and circular polarisations. [59][60][61][62] Summarizing, the ensuing results demonstrated the possibility of altering the strength of the resonance energy transfer between two nanoparticles by careful engineering of the spacing and inclusion of an ideal quantum mirror in the vicinity. Therefore, the analysis demonstrates a mechanism to inhibit or markedly enhance the transfer of energy between discrete components, potentially in any multi-quantum dot/nanowire system, inviting surface and layer applications.…”
Section: Discussionmentioning
confidence: 91%
“…Surprising effects also arise in optically very simple optical systems. One striking instance, illustrated in figure 4, occurs in the proximity of a mirror, when circularly polarized light impinges at normal incidence; it has been shown that the self-interference of reflected photons produces electromagnetic field distributions with a capacity to produce chiroptical interactions on a locally anomalous scale [9,32,33]. In addition to all of these features, novel experimental effects can also arise over the physical scale represented by the cross-section of a structured beam, as will emerge in later sections.…”
Section: Structure and Scalementioning
confidence: 99%